Awareness on nutrition among the pregnant women at a female hospital in Jessore, Bangladesh - Rahman, Md Moshiur (Mediscope, 2015)
The study assessed the awareness on nutrition among the pregnant women at Female Ad-din Hospital in Jessore, Bangladesh from December 2011 to March 2012. One hundred seventy seven newly delivered mothers were randomly selected for interview on nutrition during pregnancy. Detailed history on food intake by the mothers during pregnancy period were recorded and analyzed. Many of the respondents did not take adequate amount of rice, vegetables, pulses, protein, vitamins, iron or minerals during pregnancy. This was due to that many of the pregnant mothers were not aware about increased food intake need during pregnancy period. Considering insufficient awareness in respect to nutritional behaviors among females of reproductive age, pregnant women and those who plan for pregnancy should be educated about adequate diet. DOI: http://dx.doi.org/10.3329/mediscope.v1i1.21631 Mediscope Vol. 1, No. 1: 2014, Pages 14-18